Aberrant multimodal brain networks in patients with anti‐NMDA receptor encephalitis. (13th March 2021) - Wang, Jinhui; Duan, Yunyun; Zhang, Tian; Huang, Jing; Ren, Zhuoqiong; Ye, Jing; Wang, Ningkai; Li, Yinzhi; Chen, Xiaoya; Gao, Peiyi; Li, Kuncheng; Liu, Yaou
Abstract: Aims: To explore large‐scale brain network alterations and examine their clinical and neuropsychological relevance in patients with anti‐N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. Methods: Twenty‐four patients with anti‐NMDAR encephalitis and 26 matched healthy controls (HCs) were enrolled in our study. Based on the multimodal MRI dataset, individual morphological, structural, and functional brain networks were constructed and compared between the two groups at multiple levels. The associations with clinical/neuropsychological variables and the discriminant ability of significant alterations were further studied. Results: Multimodal network analysis revealed that anti‐NMDAR encephalitis mainly affected morphological and structural networks, but subtle alterations were observed in functional networks. Intriguingly, decreased network local efficiency was observed for both morphological and structural networks and increased nodal centrality in the lateral orbital gyrus was convergently observed among the three types of networks in the patients. Moreover, the alterations, particularly those from structural networks, accounted largely for cognitive deficits of the patients and could distinguish the diseased individuals from the HCs with excellent performance (area under the curve =0.933). Conclusions: The current study provides a comprehensive view of characteristic multimodal network dysfunction in anti‐NMDAR encephalitis, which is crucial to establish new diagnostic biomarkers and promising therapeutic targets for the disease. Abstract : The current study provides a comprehensive view of characteristic multimodal network dysfunction in anti‐N‐methyl‐D‐aspartate receptor encephalitis, which is crucial to establish new diagnostic biomarkers and promising therapeutic targets for the disease.